Mastering blockchain programming with Solidity : write production-ready smart contracts for Ethereum Blockchain with Solidity - Chittoda, Jitendra (Packt Publishing, 2019)
With this book, you will learn to write production-ready smart contracts for the Ethereum blockchain. Finally, with the help of comprehensive examples, you will learn how to add security to smart contracts and then delve into the various security considerations that must be paid attention to.